2022
DOI: 10.1101/2022.12.17.22282984
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reproducible And Clinically Translatable Deep Neural Networks For Cervical Screening

Abstract: Cervical cancer is a leading cause of cancer mortality, with approximately 90% of the 250,000 deaths per year occurring in low- and middle-income countries (LMIC). Secondary prevention with cervical screening involves detecting and treating precursor lesions; however, scaling screening efforts in LMIC has been hampered by infrastructure and cost constraints. Recent work has supported the development of an artificial intelligence (AI) pipeline on digital images of the cervix to achieve an accurate and reliable … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…This is achieved even in the absence of retraining, and remains relatively constant throughout incremental retraining, as Table 2 highlights. This is largely attributable to the presence of MC dropout and the dedicated optimization of repeatability as a selection criterion during model optimization (6,21,31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is achieved even in the absence of retraining, and remains relatively constant throughout incremental retraining, as Table 2 highlights. This is largely attributable to the presence of MC dropout and the dedicated optimization of repeatability as a selection criterion during model optimization (6,21,31).…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we utilized a model that we developed in a prior study, following a multistage model selection and optimization process utilizing a multi-heterogeneous dataset, henceforth referred to as "SEED" (21). The primary discernible axes of heterogeneity in this prior work included image capture device and geography.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1); these included different model architectures (densenet121 24 , resnet50 25 ), loss functions (standard cross-entropy, quadratic weighted kappa 26 , and mean-squared error losses) and dataset balancing strategies (balanced sampling, balanced loss). Our design choices here were informed by prior work 20 highlighting the utility of these choices across medical imaging domains, and specifically for the cervical domain.…”
Section: Model Developmentmentioning
confidence: 99%
“…However, numerous studies have indicated that visual evaluation by healthcare providers exhibits suboptimal accuracy and repeatability 18,19 , creating a necessity for automated tools that can more consistently evaluate cervical lesions and direct the appropriate treatment protocol. To this end, we had previously generated a multiclass diagnostic classifier able to classify the appearance of the cervix into "normal", "indeterminate" and "precancer/cancer" categories 20 .…”
Section: Introductionmentioning
confidence: 99%